Dynamics of knowledge production and technology diffusion: Insights from the emergence of wind energy - Sousa, Cristina (2015)
The objective of this paper is to contribute to a better understanding of the relation between the dynamics of knowledge production and technology diffusion along the process of emergence of a new technology, as it unfolds in diverse spatial locations. For this purpose, the paper traces the process of knowledge production over time – expressed in the number of scientific publications - and assesses how its dynamics relate with those of technology up-scaling and diffusion, for the case of a new renewable energy technology: wind power. It also compares these processes in different spatial areas, looking at similarities and differences in the evolving patterns, in initial markets and follower regions. In order to trace the dynamics of knowledge production we conduct a bibliometric analysis, using data collected from the Thomson Reuters Web of Science database (for the period 1970-2012). In order to trace the diffusion dynamics we use data collected on both unit scale of turbines and installed capacity of wind power (starting in late 1970s), following the empirical scaling methodology. These analyses are conducted at global scale and, subsequently, at a regional scale, for a pioneer (Denmark) and a fast follower (Portugal). The comparison of the outcomes from the bibliometric and the technology growth analyses permits to understand the rhythm and order in which knowledge was created and applied in this particular innovation. It also provides a preliminary account of the interplay between pioneer and fast follower regions.